L’Europa e la tricotomia critica kantiana: Intervista impossibile ad Immanuel Kant (Materiali di Estetica. Terza serie, 2020)
Kantian criticism re-inteprets the conflict between the "two cultures". Kant builds an architecture of thought within which knowledge and freedom are two sides of the same coin. Not only that: for Kant the keystone of this architecture is provided by hope. In the light of this indication for Kant, Europe is not a state reality, but a project of civilisation. A project to build the knowledge society by creating an ever-widening heritage of civil liberties.
Keywords: Criticism; Trascendental; Critical rationalism